Image quality enhancement by applying a combination of filtering between the median filter and CLAHE - Hsb, Adinda Tarisyah; Harahap, Lailan Sofinah; Fadillah, Hasti (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
Digital image quality is often degraded due to disturbances such as salt-and-pepper noise and uneven lighting. This can hinder further image analysis and processing. This research aims to improve image quality by applying a combination of two filtering methods, namely Median Filter and CLAHE (Contrast Limited Adaptive Histogram Equalization), using MATLAB. Median Filter is used to remove impulsive noise without obscuring important details, while CLAHE is applied to improve image contrast adaptively and locally. Tests were conducted on grayscale images with artificial noise added. The experimental results show that the combination of both methods provides a significant improvement in image quality compared to the use of either method alone. Thus, this approach is effectively used for image pre-processing that requires detail recovery and contrast enhancement.